Eleventh International Women in Surgery Career Symposium, February 14-16, 2020 Sand Key Resort, Clearwater Florida. Issue 1 (January 2022) - Ross, Sharona; Luberice, Kenneth; Rosemurgy, Alexander; ,
Surgery, society, and the world are ever changing. The role of women in surgery is changing too and changing fast. For many women, this change is too slow, too fast, too disruptive, too confusing, and too dependent on others. A symposium such as this helps direct our discussions and thoughts, but many answers will evolve only with and after thoughtful consideration, debate, and action. The symposium is not a "gripe session, " but a call to arms for all stakeholders, including surgery. Surgery must evolve commensurate with the times and recognize the huge and unique talent pool women represent. Herein is the summary of the plenary session of the symposium. Hopefully, it will stir emotions and initiate debate which will lead to enlightenment and benefit to surgery, our patients, our employers, and all surgeons, both current and future. For those who want to be part of the dialogue, please take advantage of this opportunity. This symposium will continue to be held annually as we build our awareness and develop impactful ideologies to further the beneficial impact of the surgical community. Lead, follow, or get out of the way; your choice. We encourage all to be part of the process.